Methodological reflections on artistically illustrating ethnographic text from a study of sport pedagogy in youth detention: Ethics, affect, and description - Roe, Daniel; Bäckström, Åsa (Frontiers in Sports and Active Living, 2022)
While there is a burgeoning body of literature on visual methods in ethnography, including drawing and illustration as method for collecting and exploring data, little has been written about how artistic illustrations can be used as a representational method for finished ethnographic texts. Based on an illustrated ethnography–a PhD thesis on sport pedagogy in youth detention–this paper explores what artistic illustrations can do for representations of ethnographic texts. An important starting point of the paper is that artistic illustrations are purpose-full–they can be used strategically to highlight some details over others, thus making it possible for researchers to selectively accomplish several aims when it comes to representation. Particularly, we focus on ethical, affective, and descriptive purposes for using artistic illustrations when publishing research on sport in total institutions. We present selected illustrations from the thesis together with analytical and procedural commentary to shed light on some strategic thinking behind the production of the illustrations. Finally, we conclude with some reflections on the methodology and discuss some further considerations for illustrating ethnographic texts in terms of benefits, risks, and possibilities.